PERANCANGAN HUMAN RESOURCE INFORMATION SYSTEM BERBASIS WEB PADA CV. CIPTA SARANA MAKMUR - Abednego Marcello; Bhustomy Hakim (Jurnal Teknoinfo, 2025)
The process of collecting and managing human resource data—such as attendance records, employee information, job assignments, and payroll—at CV. Cipta Sarana Makmur is currently carried out manually. This manual approach has resulted in several significant operational issues, including a high risk of data damage or loss, administrative delays, and increased workloads due to the lack of an integrated system. Furthermore, the conventional method often leads to data duplication and input errors, which negatively affect the accuracy of information, time efficiency, and the reliability of managerial decision-making. To address the identified issues, this study focuses on designing and developing a web-based Human Resource Information System (HRIS) capable of automating and integrating all human resource data management processes in an efficient and effective manner. The system development process adopts the Software Development Life Cycle (SDLC) methodology using the Waterfall model, which consists of five key phases: requirements analysis, system design, implementation, testing, and maintenance. Each phase is carried out in a structured and sequential manner to ensure the accuracy and completeness of the system being developed. Laravel was selected as the development framework due to its modular structure based on the Model-View-Controller (MVC) architecture, comprehensive documentation, and flexibility that supports efficient programming and long-term system scalability. The results demonstrate that the developed HRIS successfully meets the company’s operational needs by centralising and integrating various human resource functions. The system enables digital and structured processes for attendance tracking, employee data management, job assignment handling, and payroll processing. Its implementation significantly reduces data processing errors, avoids information redundancy, and accelerates administrative workflows that previously required considerable time when performed manually. Additionally, the system enhances data transparency and facilitates real-time information tracking, which supports better managerial oversight and decision-making. In conclusion, the HRIS developed in this study effectively addresses the core issues faced by CV. Cipta Sarana Makmur in managing human resource operations. To maximise the system’s potential, it is recommended that comprehensive training be provided to system users. For future system enhancements, the integration of more advanced technologies—such as facial recognition-based attendance systems—is advised to further improve accuracy, efficiency, and overall data security. Keyword: laravel, human resource information system, SDLC waterfall, data management, HRIS.